If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16t + -7t + -8t + -1t + t + 2 = 16 Reorder the terms: 2 + 16t + -7t + -8t + -1t + t = 16 Combine like terms: 16t + -7t = 9t 2 + 9t + -8t + -1t + t = 16 Combine like terms: 9t + -8t = 1t 2 + 1t + -1t + t = 16 Combine like terms: 1t + -1t = 0 2 + 0 + t = 16 2 + t = 16 Solving 2 + t = 16 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + t = 16 + -2 Combine like terms: 2 + -2 = 0 0 + t = 16 + -2 t = 16 + -2 Combine like terms: 16 + -2 = 14 t = 14 Simplifying t = 14
| 12=n/9=1 | | 2x-14y=-22 | | 3(2t-6)=2(3r-9) | | 5x+5(4x+12)=10 | | 2(x-3)=1/2x | | 3(n+1)-2n=0 | | -2z+13z+13z-20z=-20 | | 0=4+2n | | 13+b=-4 | | 4/7y-8=2/7y-10 | | 2x-14y=22 | | 3(4x+5)-3y=-15 | | 8-2x=-13 | | 8(-2i)(-5-4i)= | | (8(-3)-1)-(-3)+3= | | 82(0.006889-x^2)=2x | | 3x-3y=4x+5 | | 19=4-2x | | 32x-4=3 | | -16a+11a+7a=-16 | | w/- | | 82(0.006888-x^2)=2x | | -16+y=5 | | 6-a=10-9 | | 4(x-6)=21 | | -3p+13p+14=-16 | | 2*.2-3+7+7+3*.2-10= | | (3x+3)=(4x-5) | | 15(t+2)2+9t=-90 | | 2x+5(.3-2.3)=3 | | r=0.301 | | 12+6r=-4r-5-7r |